The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.21203/rs.3.rs-1110079/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and Functional Neuroplasticity Following Bilateral Vestibular Loss: A Longitudinal [18F]-UCB-H/[18F]-FDG Dual Tracer Rat Study

Abstract: Neuronal lesions trigger mechanisms of structural and functional neuroplasticity, which can support recovery. However, the temporal and spatial appearance of structure-function changes and their interrelation remain unclear. The current study aimed to directly compare serial whole-brain in vivo measurements of functional plasticity (by [18F]-FDG-PET) and structural synaptic plasticity (by [18F]-UCB-H-PET) before and after bilateral labyrinthectomy in rats and investigate the effect of locomotor training. Compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Although the details are still to be elucidated, it is becoming clear that the pedunculopontine tegmental nucleus, which is known to project to the striatum, is also connected to the vestibular nucleus; furthermore, it is evident that PD is associated with major changes in cholinergic pathways involving the vestibular system. The study by Antons et al (48) reinforces previous evidence that vestibular loss is associated with major functional changes in the striatum. Evidence continues to be reported that GVS can modulate the symptoms of PD (23).…”
Section: The Vestibular System and The Striatumsupporting
confidence: 81%
See 1 more Smart Citation
“…Although the details are still to be elucidated, it is becoming clear that the pedunculopontine tegmental nucleus, which is known to project to the striatum, is also connected to the vestibular nucleus; furthermore, it is evident that PD is associated with major changes in cholinergic pathways involving the vestibular system. The study by Antons et al (48) reinforces previous evidence that vestibular loss is associated with major functional changes in the striatum. Evidence continues to be reported that GVS can modulate the symptoms of PD (23).…”
Section: The Vestibular System and The Striatumsupporting
confidence: 81%
“…Antons et al (48) undertook a large longitudinal dual tracer study in rats following BVL, using positron emission tomography with computer tomography to measure functional and structural plasticity throughout the brain at 1, 3, 5, 7, and 9 weeks post-lesion. They found significant decreases in glucose metabolism in both the left and right striatum, coupled with increases in synaptic density.…”
Section: The Vestibular System and The Striatummentioning
confidence: 99%